2022
DOI: 10.3389/fmicb.2022.769008
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Protoplast Preparation and Establishment of Genetic Transformation System of an Arctic-Derived Fungus Eutypella sp.

Abstract: Arctic-derived fungus Eutypella sp. D-1 has attracted wide attention due to its huge ability to synthesize secondary metabolites. However, current studies only focus on stimulating its production of new secondary metabolites by OSMAC strategies, and the relationship between secondary metabolites and biosynthetic gene clusters (BGCs) has not been explored. In this study, the preparation and regeneration conditions of Eutypella sp. D-1 protoplasts were explored to lay a foundation for the study of genetic transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Thus, we used several existing protoplast isolation methods as the basis for developing a simple yet efficient method for protoplast generation from Lophiotrema sp. F6932 ( Abdallah et al, 2017 ; Roth and Chilvers, 2019 ; Ning et al, 2022 ). Preliminary studies had shown that potato dextrose broth (PDB) was the best media for generating mycelia for protoplast isolation from this fungus compared with two other media; malt extract broth and Sabouraud dextrose broth ( Supplementary Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, we used several existing protoplast isolation methods as the basis for developing a simple yet efficient method for protoplast generation from Lophiotrema sp. F6932 ( Abdallah et al, 2017 ; Roth and Chilvers, 2019 ; Ning et al, 2022 ). Preliminary studies had shown that potato dextrose broth (PDB) was the best media for generating mycelia for protoplast isolation from this fungus compared with two other media; malt extract broth and Sabouraud dextrose broth ( Supplementary Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, selection of an appropriate type and concentration of an osmotic stabilizer in the protoplasting medium is critical in preventing lysis or shriveling of protoplast due to osmotic stress ( Ren et al, 2018 ; De Wu and Chou, 2019 ). Other than the enzymes and osmotic stabilizers, other factors such as enzymatic hydrolysis temperature, duration of incubation, fungal age and mycelium status need to be optimized for each strain ( Jin et al, 2020 ; Ning et al, 2022 ). For example, depending on whether the fungal strain is slow or fast-growing, very short culture time may yield less mycelium and thus low yield of protoplast.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations